STUDI PERBANDINGAN BIAYA BAHAN PADA BEKISTING KAYU DAN BONDEK DI GEDUNG FAKULTAS ILMU PENDIDIKAN UNIVERSITAS TRIBHUWANA TUNGGADEWI MALANG - Pakereng, Roly; Wijaya, Handika Setya (Universitas Tribhuwana Tunggadewi Malang, 2019)
At this time technological advances the world construction intensified. In improving the quality of the work of a construction, numerous attempts have been made to get the work more effective, efficient and quality values fixed in the preserve. So also with the method of implementation of the floor plate using wood formwork in compare with bondek on the work floor plate building of the Faculty of education at the University of Tribhuwana Tunggadewi Malang, in the work floor plates using plate further simplify and accelerate bondek a floor plate work on the building. In this research aims to know the difference between the cost of the execution of the work plate floor using wooden formwork bondek compared to on the job building of the Faculty of education at the University of Tribhuwana Tunggadewi Malang. In the collection of data, the researchers used a method of observation and the method of literature. From this research it was concluded that the cost of implementation of the work plate formwork timber floors with cost of 368,021,577.00 more expensive compared to a cost of bondek plate 133.027.125.00